WAYS TO REDUCE HYDRATION AND CRACKING OF CONCRETE IN THE PRODUCTION OF SPECIAL REINFORCED CONCRETE PRODUCTS (British Journal of Global Ecology and Sustainable Development, 2023)
The article presents the results of an experimental study of the ways to reduce the dehydration of the concrete mixture and the formation of cracks in reinforced concrete products during their manufacture.